THE CONTEXTUAL EFFECT OF SCHOOL ON SELF-CARE IN CHILDREN WITH MENTAL RETARDATION IN SURAKARTA, CENTRAL JAVA - Wayanshakty, Janur Putri; Dewi, Yulia Lanti Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background: WHO analysis estimates the number of children with disabilities reaching 7-10% of the total population of children. The limitations of retarded children are influenced by age, physical condition, nutritional status of the child, and parenting in the family have a relationship in the level of independence of the children. The purpose of this study was to analyze the factors that influence self-care in retarded children in Surakarta, Central Java.Subjects and Method: This study was a cross sectional study conducted in 15 special schools in Surakarta, Central Java, from June to July 2019. A sample of 200 mentally retarded children aged 9-17 years was selected by stratified random sampling. The dependent variable was self care. The independent variables were age, nutritional status, mental retardation classification, maternal age, maternal education, maternal occupation, maternal knowledge, parenting style, and teacher support in school. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Good self-care in mentally retarded children increased with aged ?15 years (b= 4.61; 95% CI= 2.53 to 6.69; p<0.001), mild retardation (b= 2.02; 95% CI= 0.13 to 3.91; p= 0.036), maternal education ?senior high school (b= 1.23; 95% CI= 0.22 to 2.25; p= 0.017), and good maternal parenting style (b= 1.42; 95% CI= 0.21 to 2.62; p= 0.021). Good self-care decreased with undernourished children (b= -2.16; 95% CI= -3.44 to -0.87; p= 0.001), low maternal knowledge (b= -1.56; 95% CI= -2.90 to -0.22; p= 0.023), and weak teacher support (b= -3.34; 95% CI= -5.41 to -1.26; p= 0.002).Conclusion: Good self-care in mentally retarded children increases with aged ?15 years, mild retardation, maternal education ?senior high school, and good maternal parenting style. Good self-care decreases with undernourished children, low maternal knowledge, and weak teacher support.Keywords: self-care, mental retardation, childrenCorrespondence: Janur Putri Wayanshakty. Masters program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: janurputri@gmail.com. Mobile: 085258870014Journal of Maternal and Child Health (2020), 5(1): 19-27https://doi.org/10.26911/thejmch.2020.05.01.03